2020
DOI: 10.1016/j.celrep.2020.108122
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Neutralizing Antibody Epitope Specificities to an HIV Env Trimer in Immunized and in Infected Rhesus Macaques

Abstract: Summary BG505 SOSIP is a well-characterized near-native recombinant HIV Envelope (Env) trimer that holds promise as part of a sequential HIV immunogen regimen to induce broadly neutralizing antibodies (bnAbs). Rhesus macaques are considered the most appropriate pre-clinical animal model for monitoring antibody (Ab) responses. Accordingly, we report here the isolation of 45 BG505 autologous neutralizing antibodies (nAbs) with multiple specificities from SOSIP-immunized and BG505 SHIV-infected rhesus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 63 publications
5
34
0
Order By: Relevance
“…To gain further insight into the specificities of serum nAbs targeting the 465 glycan hole, we performed additional mapping experiments using three mutants that have been used to define recognition of sites within the BG505 C3/465 epitope cluster [ 12 , 19 ]. These mutants shift (TI357KT) or remove (T357A to remove N355; N398A knock out) glycans in this region ( S2 Fig ) [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To gain further insight into the specificities of serum nAbs targeting the 465 glycan hole, we performed additional mapping experiments using three mutants that have been used to define recognition of sites within the BG505 C3/465 epitope cluster [ 12 , 19 ]. These mutants shift (TI357KT) or remove (T357A to remove N355; N398A knock out) glycans in this region ( S2 Fig ) [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Neutralization against HIV-1 Env BG505.T332N (derived from BG505.W6M.Env.C2, Genbank accession #DQ208458), BG505.W6M.C2 containing T332, and ten HIV-1 BG505.T332N mutants described in [ 5 , 12 , 19 ] were measured using serially diluted, heat-inactivated immunized RM serum or mAbs in the TZM-bl assay as previously described, using cells plated one day prior to the assay [ 28 , 32 , 34 46 ]. In brief, Env PV was generated by transfecting the Env-expressing plasmid DNA alongside the HIV-1 SG3ΔEnv proviral backbone DNA into 293T cells, using the Fugene HD reagent as recommended (E2312, Promega).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutralization potential of the C3/V5 epitope in BG505 has been reported previously (Lei et al, 2019, Nogal et al, 2020a, Zhao et al, 2020, Cirelli et al, 2019. Antibodies bound to this site can sterically block CD4 binding, which represents a potential mechanism of virus neutralization.…”
Section: Cryoempem Analysis Of the Bg505-specific Polyclonal Antibodymentioning
confidence: 68%
“…This antibody class can interact with the BG505 SOSIP.v3 antigen (Figure S1C; depicted in light green) and is likely responsible for the serum neutralization observed for animal Rh.33172 at the week 38 time point. Previous studies have shown that V1-targeting antibodies in BG505 can be moderately neutralizing (Klasse et al, 2018, Zhao et al, 2020, Nogal et al, 2020a).…”
Section: Resultsmentioning
confidence: 98%